Targeting CD137 (4-1BB) towards improved safety and efficacy for cancer immunotherapy - Liu, Guizhong; Luo, Peter (Frontiers in Immunology, 2023)
T cells play a critical role in antitumor immunity, where T cell activation is regulated by both inhibitory and costimulatory receptor signaling that fine-tune T cell activity during different stages of T cell immune responses. Currently, cancer immunotherapy by targeting inhibitory receptors such as CTLA-4 and PD-1/L1, and their combination by antagonist antibodies, has been well established. However, developing agonist antibodies that target costimulatory receptors such as CD28 and CD137/4-1BB has faced considerable challenges, including highly publicized adverse events. Intracellular costimulatory domains of CD28 and/or CD137/4-1BB are essential for the clinical benefits of FDA-approved chimeric antigen receptor T cell (CAR-T) therapies. The major challenge is how to decouple efficacy from toxicity by systemic immune activation. This review focuses on anti-CD137 agonist monoclonal antibodies with different IgG isotypes in clinical development. It discusses CD137 biology in the context of anti-CD137 agonist drug discovery, including the binding epitope selected for anti-CD137 agonist antibody in competition or not with CD137 ligand (CD137L), the IgG isotype of antibodies selected with an impact on crosslinking by Fc gamma receptors, and the conditional activation of anti-CD137 antibodies for safe and potent engagement with CD137 in the tumor microenvironment (TME). We discuss and compare the potential mechanisms/effects of different CD137 targeting strategies and agents under development and how rational combinations could enhance antitumor activities without amplifying the toxicity of these agonist antibodies.